Cultural Heritage: A Systematic Literature Review - Halaç, Hicran Hanım; Bademci, Fikret (Karabük Üniversitesi, 2021)
International organizations such as UNESCO, ICOMOS, ICCROM, which play an important role in the protection, preservation and transfer of cultural heritage to the future, try to increase the consciousness-raising and awareness of people about cultural heritage with their work. In addition, it supports researchers to work on cultural heritage and contributes to the scientific study of the subject. This situation allows to increase cultural heritage studies in the world of science. This review aims to systematically examine the theses written on cultural heritage in the context of education, promotion, consciousness-raising and awareness. The scope of the study has been determined as the National Thesis Center website where the theses, in Turkey, made since the establishment of YÖK are located. In the advanced screening section on the website of the National Thesis Center, the theses resulting from the different combinations of the cultural heritage keyword education, promotion, consciousness-raising and awareness were examined in detail. As a result of the examination, it was seen that while the intensity of master's theses was noteworthy, different methods were used in the theses and interview was the most preferred among these methods.

UNESCO, ICOMOS, ICCROM gibi kültürel mirasların korunması, yaşatılması ve geleceğe aktarılmasında önemli rol oynayan uluslararası örgütler yapmış oldukları çalışmalar ile insanların kültürel miras konusundaki bilinç ve farkındalıklarını arttırmaya çalışmaktadır. Bu kuruluşlar ayrıca araştırmacıların kültürel miras konusunda çalışmalar yapmalarını destekleyerek konunun bilimsel literatürünün gelişmesine katkı sağlamaktadır. Bu durum bilim dünyasında kültürel miras çalışmalarının arttırılmasına olanak sağlamaktadır. Bu derleme çalışma, kültürel miras ile ilgili yazılmış tezleri eğitim, tanıtım, bilinçlendirme ve farkındalık bağlamında sistematik bir biçimde ayrıntılı olarak incelemeyi amaçlamaktadır. Çalışmanın kapsamı Türkiye’de YÖK’ün kuruluşundan itibaren yazılmış olan tezlerin bulunduğu Ulusal Tez Merkezi internet sitesi olarak belirlenmiştir. Ulusal Tez Merkezi internet sitesinde yer alan gelişmiş tarama bölümünde kültürel miras anahtar kelimesinin eğitim, tanıtım, bilinçlendirme ve farkındalık anahtar kelimeleriyle oluşturulan farklı kombinasyonlar sonucunda ortaya çıkan tezler detaylıca incelenmiştir. İnceleme sonucunda yüksek lisans tezlerinin yoğunluğu dikkat çekerken tezlerde farklı yöntemlerin kullanıldığı ve bu yöntemler içerisinde en çok görüşmenin tercih edildiği görülmüştür.
KÜLTÜREL MİRAS: SİSTEMATİK LİTERATÜR İNCELEMESİ
Keywords: Cultural Studies; Kültürel çalışmalar